Meta Analisis Pengaruh E Modul Terhadap Pengetahuan Berfikir Kritis & Kreatif Peserta Didik Dalam Pembelajaran IPA - Asrizal Asrizal; Marjuni Marjuni; Rahmi Habibah; Sintya Asiah (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to analyze the effect of the e-module on students' critical and creative thinking knowledge in science learning. This research uses a quantitative descriptive research type with meta-analysis. Data or sources are obtained from articles published in international and national journals that are selected based on categories, namely those related to the influence of e-modules on students' critical and creative thinking knowledge. There were 20 articles used in this study which were then coded and analyzed for their effect size. Based on the results of data analysis, the effect size results for knowledge of critical thinking are in the very high category, for knowledge of creative thinking also has the very high category, meanwhile, the effect of the e-module on students' critical and creative thinking knowledge based on junior high school, senior high school and tertiary education levels has a very high category. Then in the science field, namely Physics, Chemistry, Biology lessons, they have an effect size in the very high category. The results of the analysis show that the effect of the e-module on students' critical and creative thinking knowledge is very high